Phenylalanine hydroxylase mRNA rescues the phenylketonuria phenotype in mice - Cacicedo, Maximiliano L.; Weinl-Tenbruck, Christine; Frank, Daniel; Limeres, Maria Jose; Wirsching, Sebastian; Hilbert, Katja; Pasha Famian, Mansure Abdollah; Horscroft, Nigel; Hennermann, Julia B.; Zepp, Fred; Chevessier-Tünnesen, Frédéric; Gehring, Stephan (Frontiers in Bioengineering and Biotechnology, 2022)
Phenylketonuria (PKU) is an inborn error of metabolism caused by a deficiency in functional phenylalanine hydroxylase (PAH), resulting in accumulation of phenylalanine (Phe) in patients’ blood and organs. Affected patients encounter severe developmental delay, neurological deficits, and behavioral abnormalities when not treated. Early diagnosis and treatment are extremely important; newborn screening programs have been implemented in most countries to ensure early identification of patients with PKU. Despite available treatment options, several challenges remain: life-long adherence to a strict diet, approval of some medications for adults only, and lack of response to these therapies in a subpopulation of patients. Therefore, there is an urgent need for treatment alternatives. An mRNA-based approach tested in PKU mice showed a fast reduction in the accumulation of Phe in serum, liver and brain, the most significant organ affected. Repeated injections of LNP-formulated mouse PAH mRNA rescued PKU mice from the disease phenotype for a prolonged period of time. An mRNA-based approach could improve the quality of life tremendously in PKU patients of all ages by replacing standard-of-care treatments.